Analysis of the features of existing and perspective methods of metrological verification (calibration) of level gauges - Pasternak, Volodymyr; Brynchak, Dmytro (Видавництво Львівської політехніки, 2025)
The primary purpose of this scientific article is to analyze existing and potential methods of metrological verification (calibration) of level gauges used for accurate metering of oil products in tanks of various types and purposes. This study will consider their key features, advantages, and disadvantages, as well as prospects for development and improvement, considering modern technological advances and requirements of industry standards.
Keywords: level gauge; level measurement system; calibration method